Analisa Platform Library Steam Sebagai Data Aset Manajemen - Egi Abinowi; Dudih Gustian (Jurnal Komputer dan Sistem Informasi, 2025)
Data has transformed into a strategic asset with high economic value, especially in the gaming industry through digital distribution platforms such as Steam. This study aims to analyze the Steam library platform as a form of Data Asset Management (DAM) implementation. Through a review of various library features, this study explores how user interactions including purchase history, playtime, achievements, and genre preferences are managed as structured digital asset data units. The analysis shows that Steam performs the main functions of asset management which include storing, managing, utilizing, and analyzing data to generate added value for users and the company. This data utilization is realized through personalized services, such as the "Play Next" recommendation system and more effective marketing strategies. In conclusion, the Steam library is not just a collection of games, but an ecosystem of digital data assets that are systematically managed to create economic and strategic value, while increasing user loyalty and engagement on the platform.